Math, asked by khanhafsa7022, 11 months ago

if the sum of the first 4terms of an Ap is 40 and that of first 14 terms is 280find the sum of the first n term

Answers

Answered by SarcasticL0ve
11

 \sf{ \sf S_n = n^2 + 6n}

Given:-

  •  \sf{Sum\;of\;first\;4\;terms\;of\;an\;AP\;( \sf S_4 ) = 40}

  •  \sf{Sum\;of\;first\;14\;terms\;of\;an\;AP\;( \sf S_{14} ) = 280}

To Find:-

  •  \sf{Sum\;of\;first\;n\;terms\;of\;an\;AP\;( \sf S_n ) = ?}

Solution:-

\small \; \; \; \star \; {\underline{\underline{\sf{\red{Sum\;of\;n\;terms\;of\;AP\;:}}}}}

{\underline{\boxed{\sf{\dag\; \sf S_n = \dfrac{n}{2} \bigg( 2a + (n - 1)d \bigg)}}}}

\small \; \; \; \star \; {\underline{\underline{\sf{\red{Sum\;of\;4\;terms\;of\;AP\;:}}}}}

: \implies \sf{ \sf S_4 = \cancel{ \dfrac{4}{2}} \bigg( 2a + (4 - 1)d \bigg)}

: \implies \sf{40 = 2 \bigg( 2a + 3d \bigg)}

: \implies \sf{ \cancel{ \dfrac{40}{2}}= 2a + 3d}

: \implies \sf{20 = 2a + 3d} ---- eq.(1)

Similarly,

\small \; \; \; \star \; {\underline{\underline{\sf{\red{Sum\;of\;14\;terms\;of\;AP\;:}}}}}

: \implies \sf{ \sf S_{14}  = \cancel{ \dfrac{14}{2}} \bigg( 2a + (14 - 1)d \bigg)}

: \implies \sf{280 = 7 \bigg( 2a + 13d \bigg)}

: \implies \sf{ \cancel{ \dfrac{280}{7}} = 2a + 13d}

: \implies \sf{40 = 2a + 13d} ---- eq.(2)

\rule{200}{2}

\small \; \; \; \star \; {\underline{\underline{\sf{Subtracting\;eq(2)\;from\;eq(1):}}}}

we get,

: \implies \sf{-10d = -20}

: \implies \sf{d = \cancel{ \dfrac{-20}{-10}}}

: \implies {\underline{\sf{\purple{d = 2}}}}

\small \; \; \; \star \; {\underline{\underline{\sf{Putting\;value\;of\;d\;in\;eq(1):}}}}

: \implies \sf{20 = 2a + 3 \times 2}

: \implies \sf{20 = 2a + 6}

: \implies \sf{20 - 6 = 2a}

: \implies \sf{14 = 2a}

: \implies \sf{a} = \cancel{ \dfrac{14}{2}}

: \implies {\underline{\sf{\purple{a = 7}}}}

\rule{200}{2}

★ Now, we have value of a and d

\small \; \; \; \star \; {\underline{\underline{\sf{Putting\;value\;of\;a\;and\;d\;in:}}}}

{\underline{\boxed{\sf{\dag\; \sf S_n = \dfrac{n}{2} \bigg( 2a + (n - 1)d \bigg) }}}}

: \implies \sf{ \sf S_n = \dfrac{n}{2} \bigg( 2 \times 7 + (n - 1)2 \bigg) }

: \implies \sf{ \sf S_n = \dfrac{n}{2} \bigg( 14 + 2n - 2 \bigg) }

: \implies \sf{ \sf S_n = \dfrac{n}{2} \bigg( 2n + 12 \bigg) }

: \implies \sf{ \sf S_n = \dfrac{2n^2}{2} + \dfrac{12n}{2}}

: \implies \sf{ \sf S_n = \dfrac{ \cancel{2} n^2}{ \cancel{2}} + \dfrac{ \cancel{12} n}{ \cancel{2}}}

: \implies \sf{ \sf S_n = n^2 + 6n}

{\underline{\underline{\sf{\purple{\dag \; Hence\;Solved!}}}}}

\rule{200}{2}

Answered by Anonymous
9

\sf\red{\underline{\underline{Answer:}}}

\sf{The \ sum \ of \ first \ n \ terms \ is \ n(n+6)}

\sf\orange{Given:}

\sf{In \ an \ AP,}

\sf{\implies{Sum \ of \ first \ 4 \ terms \ (S4)=40}}

\sf{\implies{Sum \ of \ first \ 14 \ terms \ (S14)=280}}

\sf\orange{To \ find:}

\sf{The \ sum \ of \ first \ n \ term \ (Sn).}

\sf\green{\underline{\underline{Solution:}}}

\boxed{\sf{Sn=\frac{n}{2}[2a+(n-1)d]}}

\sf{According \ to \ the \ first \ condition.}

\sf{S4=\frac{4}{2}[2a+(4-1)d]}

\sf{\therefore{40=2\times[2a+3d]}}

\sf{\therefore{2a+3d=\frac{40}{2}}}

\sf{\therefore{2a+3d=20...(1)}}

\sf{According \ to \ the \ second \ condition.}

\sf{S14=\frac{14}{2}[2a+(14-1)d]}

\sf{\therefore{280=7\times[2a+6d]}}

\sf{\therefore{2a+13d=\frac{280}{7}}}

\sf{\therefore{2a+13d=40...(2)}}

\sf{Subtract \ equation (1) \ from \ equation (2)}

\sf{2a+13d=40}

\sf{-}

\sf{2a+3d=20}

_____________________

\sf{10d=20}

\boxed{\sf{\therefore{d=2}}}

\sf{Substitute \ d=2 \ in \ equation (1)}

\sf{2a+3\times2=20}

\sf{\therefore{2a+6=20}}

\sf{\therefore{2a=14}}

\sf{\therefore{a=\frac{14}{2}}}

\boxed{\sf{\therefore{a=7}}}

_____________________________________

\sf{Here, \ a=7 \ and \ d=2}

\boxed{\sf{Sn=\frac{n}{2}[2a+(n-1)d]}}

\sf{\therefore{Sn=\frac{n}{2}[2(7)+(n-1)\times2]}}

\sf{\therefore{Sn=n\times[7+(n-1)]}}

\sf{\therefore{Sn=n\times[n+6]}}

\sf{\therefore{Sn=n^{2}+6n}}

\sf{\therefore{Sn=n(n+6)}}

\sf\purple{\tt{\therefore{The \ sum \ of \ first \ n \ terms \ is \ n(n+6)}}}

Similar questions